ICT TECHNIQUES IN HIGHER EDUCATION: AZERBAIJAN EXPERIENCE IN PANDEMIC - Abasova Samira Huseyn qizi (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология, 2023)
The purpose of the article is to study the use of ICT techniques in Azerbaijan higher education. The objectives of the study are: 1) to substantiate the role of ICT sector in the Azerbaijan national economy, 2) to study the use of ICT sector tools in higher education, in particular in Azerbaijan higher education, 3) to analyse the external factors affecting the implementation of ICT sector tools in Azerbaijan higher education, 4) to analyse internal factors influencing the educational process in Azerbaijan higher education in with the use of ICT techniques and 5) to provide expert assessment of the use of ICT techniques in Azerbaijan higher education. The research methods are the analysis of statistical data, their grouping and comparison, expert evaluation of external (PEST analysis) and internal factors (SWOT analysis) that affect the use of ICT technologies in Azerbaijan higher education. Here were used the statistical data of Azerbaijan State Statistics Committee, electronic pages and internal reports of the Azerbaijan State University of Economics – UNEC. To reveal the role of ICT sector in the national economy, here were used the data for 2015-2022, and data for 2000/01-2021/22 academic years to analyse the activities of Azerbaijan higher education. The main questions of the study were: 1) Is the ICT sector of Azerbaijan sufficiently developed for the application of electronic spheres in the field of banking services, trade, commerce, as well as in the field of medical services and education?; 2) Is the level of ICT techniques provided sufficient for their active application in the field of Azerbaijan higher education?; 3) How has the pandemic contributed to the accelerated use of electronic services – e-education, e-training, e-conference, DocuSign, e-banking etc.? PEST analysis of political, economic, social and technological factors has been conducted and demonstrated the positive and negative assessment of ICT techniques in higher education in Azerbaijan. It has been shown that in a pandemic situation there are both positive and negative aspects of online classes as regards in the fields of techniques, methodology and psychological features. The most significant conclusions concerning ICT implementation in higher education in Azerbaijan after the pandemic have been shown. They cover the following positions: in Azerbaijan, which has 2 artificial satellites, the speed and volume of ICT services should increase; state institutions should support the high level of ICT services in Azerbaijan; both educators and students must have excellent digital skills; control of the quality of education during online education, the use of different tools and technologies in training should take the main place; regular dialogue and feedback should be carried out remotely. SWOT-analysis has been used to examine the opportunities of the ICT sector in higher education in Azerbaijan. It has been established that in the current situation in the Azerbaijanian higher education system, more flexible and optimal content, as well as the implementation of teaching strategies, and the expansion of initiatives related to the promotion of innovations have come to the fore. In the field of higher education attention is paid to the application of distance education, solving and developing the issues of technological equipment and providing quality internet connection. Yet another important direction of the state strategy is improvement of the legislative framework related to the new digital forms of education, as well as development of digital skills of pedagogical staff and students of HEI. Thus, the new world’s situation significantly changes the legal, economic, organizational and managerial regime of HEI functioning. On the one hand, significant investments are needed in new distance learning technologies that ensure the transfer of the educational process into the format of indirect (remote) interaction between teachers and students. On the other hand, it is necessary to take a decision on organizing the remote functioning of educational organizations as objects of management, creation of fundamentally new content, and the retraining of teaching and administrative personnel to ensure their readiness to work with the use of ICT techniques.